Chondroitin sulfate attenuates formalin-induced persistent tactile allodynia - Wataru Nemoto; Kotaro Yamada; Yoshiki Ogata; Osamu Nakagawasai; Katsuhito Onodera; Hidetomo Sakurai; Koichi Tan-No (Elsevier, 2016)
We examined the effect of chondroitin sulfate (CS), a compound used in the treatment of osteoarthritis and joint pain, on the formalin-induced tactile allodynia in mice. A repeated oral administration of CS (300 mg/kg, b.i.d.) significantly ameliorated the formalin-induced tactile allodynia from day 10 after formalin injection. On day 14, the phosphorylation of spinal p38 MAPK and subsequent increase in c-Fos-immunoreactive dorsal lumbar neurons were attenuated by the repeated administration of CS. These findings suggest that CS attenuates formalin-induced tactile allodynia through the inhibition of p38 MAPK phosphorylation and subsequent up-regulation of c-Fos expression in the dorsal lumbar spinal cord.